2009
DOI: 10.1007/s10661-009-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal fractionation study on bed sediments of Hussainsagar Lake, Hyderabad, India

Abstract: Hussainsagar Lake in the heart of Hyderabad City (India) receives toxic substances through five streams draining from a catchment area of 245 km(2). Of particular interest are heavy metals received from urban runoff as well as municipal sewage and industrial effluents. Heavy metals entering the lake get adsorbed onto the suspended sediments, which eventually settle down in the bottom of the lake. In this study, fractionation of metal ions has been studied on the bed sediments of Hussainsagar Lake in order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In addition, the extractable fractionation profile of Mn indicated that it is mostly bound to the residual and frac 1 in the sediment of the Beiyunhe River. These findings are similar to those of a study conducted by Jain et al (2009).…”
Section: Metal Fractionation Distribution Characteristicssupporting
confidence: 91%
“…In addition, the extractable fractionation profile of Mn indicated that it is mostly bound to the residual and frac 1 in the sediment of the Beiyunhe River. These findings are similar to those of a study conducted by Jain et al (2009).…”
Section: Metal Fractionation Distribution Characteristicssupporting
confidence: 91%
“…The residue fraction is very stable and nearly nontoxic and it is difficult to be transformed for this fraction. [13,14] Present results suggest the weak migration and release potential of As. Due to high As concentration for S6 and S7, however, As still exhibited certain potentially biological toxicity and high mobility, [36,37] especially in the sediments with low pH and ORP ( Table 2).…”
Section: The Major Physiochemical Parameters and Total Concentrationsmentioning
confidence: 65%
“…[11,12] However, the total amount analysis of the heavy metals cannot fully reflect environmental behavior and ecological effect of heavy metals in the sediments. [13,14] The migration and transformation process, biological toxicity, and bioavailability of heavy metals in the sediment mainly depend on the fractionation of heavy metal, [15,16] while the forms of heavy metals is closely associated with the toxic effects and ecological risk of the sediments. [17] The speciation of metals in sediments is therefore a critical factor in assessing the potential environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Major contaminated sites in Greater Hyderabad = Tri cities (Hyderabad, Secunderabad and Cyberabad) H Hussain Sagar, J Jawaharnagar, K Katteda M Musi river, N Nakkavagu, P Patancheru Bholakpur area - Abdul et al (2012) Municipal solid waste dumping sites -Jawaharnagar - Ahmed et al 2011;Parth et al 2009Parth et al , 2011 Industrial waste contaminated areas - Ahmed et al (2011), Balanagar, Machender et al (2011 Kattedan - Sekhar et al (2006), Govil et al (2008Govil et al ( , 2012 Hussainsagar lake sediments -PTE -Gurunadha Rao et al (2004Rao et al ( , 2008, Jain et al (2010), Suneela et al (2008), Vikram Reddy et al (2012 Industrially contaminated sites of Hyderabad -Sekhar et al (2003 Patancheru Industrial Area - Dasaram et al (2011), Govil et al (2001 …”
Section: Fig 76mentioning
confidence: 99%